Nature and deliberation in Bessarion’s De natura et arte - Marchetto, Monica (Byzantinische Zeitschrift, 2015)
The present contribution will concentrate on the central issue discussed by Bessarion in one of his major works, the De natura et arte (written in 1458 and published in 1469 as the sixth book of Bessarion’s In calumniatorem Platonis), i. e. the concept of deliberation and the relationship between nature, purposiveness and deliberation. In De natura et arte Bessarion responds to an attack by George of Trebizond, who had demonstrated, against Bessarion, not only that nature does not deliberate, but also that deliberation cannot be attributed to God who guides nature either, since deliberation implies doubt and ignorance. In this contribution I will examine the strategies Bessarion uses in order to reaffirm the possibility of attributing deliberation even to God and the arguments through which he succeeds in stressing the fundamental agreement on this subject not only between Plato and Aristotle, but also and more importantly between Plato and Christian theology.